همة الطلاب في الأنشطة اللغوية يوم الأربعاء في قسم تدريس اللغة العربية بالجامعة الإسلامية الحكومية بنجكولو - Fadhila Suskha (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2018)
AbstractTo uncover the causes that give rise to a lack of student interest in participating in language activities. To uncover strategies to increase student interest in participating in language activities in Arabic Language Study Program Faculty of Education and Teaching in IAIN Bengkulu.In this study, researchers used a qualitative descriptive approach. Data collection methods for this study by observation, interviews and documents. Language activities include teaching and learning activities every Wednesday, Weekly Arabic activities, vocabulary sharing activities, lectures, dramas. Lack of a clear curriculum led to the failure to achieve the objectives of this activity, the lack of relationship between teachers and students, the relationship between students and the students because many students does not make affect other students, the lack of discipline in the MLA, no media to learn.Key Word: Enthusiasm of students; Language activity; Teaching Arabic